Optimization of electrospun poly(N-isopropyl acrylamide) mats for the rapid reversible adhesion of mammalian cells - Cicotte, Kirsten N. (Biointerphases, 2017)
Poly(N-isopropyl acrylamide) (pNIPAM) is a “smart” polymer that responds to changes in altering temperature near physiologically relevant temperatures, changing its relative hydrophobicity. Mammalian cells attach to pNIPAM at 37 °C and detach spontaneously as a confluent sheet when the temperature is shifted below the lower critical solution temperature (∼32 °C). A variety of methods have been used to create pNIPAM films, including plasma polymerization, self-assembled monolayers, and electron beam ionization. However, detachment of confluent cell sheets from these pNIPAM films can take well over an hour to achieve potentially impacting cellular behavior. In this work, pNIPAM mats were prepared via electrospinning (i.e., espNIPAM) by a previously described technique that the authors optimized for cell attachment and rapid cell detachment. Several electrospinning parameters were varied (needle gauge, collection time, and molecular weight of the polymer) to determine the optimum parameters. The espNIPAM mats were then characterized using Fourier-transform infrared, x-ray photoelectron spectroscopy, and scanning electron microscopy. The espNIPAM mats showing the most promise were seeded with mammalian cells from standard cell lines (MC3T3-E1) as well as cancerous tumor (EMT6) cells. Once confluent, the temperature of the cells and mats was changed to ∼25 °C, resulting in the extremely rapid swelling of the mats. The authors find that espNIPAM mats fabricated using small, dense fibers made of high molecular weight pNIPAM are extremely well-suited as a rapid release method for cell sheet harvesting.